Farming as Financial Asset Global Finance and the Making of Institutional Landscapes - Ouma, Stefan (Economic Transformations, 2020)
Since the global financial crisis, the world has seen a stark rise in financial investment in farming and agricultural production. Indeed, finance has been identified as one of the main causes of the so-called "global land rush". In a world with a growing population that needs to be fed, the financial returns from agriculture are sold as safe bets. The debate that this has prompted has been frequently alarmist, with financiers blamed for rising land prices, corporate enclosures, the dispossession of smallholder farmers and the expansion of large-scale industrial agriculture. Stefan Ouma speaks to these concerns via an ethnographic journey through the agrifocused asset management industry. His penetrating analysis of case studies taken from New Zealand and Tanzania allows him to put global finance "in place", bringing into view the flesh-and-blood institutions, globespanning social relations, everyday practices and place-based value struggles that are often absent in broad-brushed narratives on the "financialization of agriculture". The book closes with a key question for the Anthropocene: which form of finance forwhich kind of food future?